Navigating student visas in the United States: Policy, practice, and implications (Comparative & International Education Series, 2021)
Navigating visa policies is an experience shared by all international students, yet discussion is limited on the important issue of attaining and maintaining status. Engaging with student visa policies begins before a student matriculates into university, follows students through their degree programs, and shapes post-graduation experiences. We offer a critical account of how visa policies permeate the entirety of student experiences on and off campus by detailing how institutions carry out federal regulation relating to student visas. We present a critical policy analysis and literature review through a chronological narrative of the international student journey through US higher education. We take a scholar/practitioner approach to bridge fields and integrate discussions from the research literature and field-specific guidance and regulations related to F-1 student visas. We aim to better inform conversations around student success that can take into account the additional challenges that exist due to student visa considerations.